Hospitalization with acute exacerbation of chronic obstructive pulmonary disease and associated health resource utilization: A population-based Danish cohort study. (July 2013) - Johannesdottir, Sigrun A.; Christiansen, Christian F.; Johansen, Martin B.; Olsen, Morten; Xu, Xiao; Parker, Joseph M.; Molfino, Nestor A.; Lash, Timothy L.; Fryzek, Jon P.
Abstract Objective: Health resource utilization (HRU) and outcomes associated with acute exacerbation of chronic obstructive pulmonary disease (AECOPD) are not well described. Therefore, a population-based cohort study was conducted to characterize patients hospitalized with AECOPD with regard to HRU, mortality, recurrence, and predictors of readmission with AECOPD. Methods: Using Danish healthcare databases, this study identified COPD patients with at least one AECOPD hospitalization between 2005–2009 in Northern Denmark. Hospitalized AECOPD patients' HRU, in-hospital mortality, 30-day, 60-day, 90-day, and 180-day post-discharge mortality and recurrence risk, and predictors of readmission with AECOPD in the year following study inclusion were characterized. Results: This study observed 6612 AECOPD hospitalizations among 3176 prevalent COPD patients. Among all AECOPD hospitalizations, median length of stay was 6 days (interquartile range [IQR] 3–9 days); 5 days (IQR 3–9) among those without ICU stay and 11 days (IQR 7–20) among the 8.6% admitted to the ICU. Mechanical ventilation was provided to 193 (2.9%) and non-invasive ventilation to 479 (7.2%) admitted patients. In-hospital mortality was 5.6%. Post-discharge mortality was 4.2%, 7.8%, 10.5%, and 17.4% at 30, 60, 90, and 180 days, respectively. Mortality and readmission risk increased with each AECOPD hospitalization experienced in the first year of follow-up. Readmission at least twice in the first year of follow-up was observed among 286 (9.0%) COPD patients and was related to increasing age, male gender, obesity, asthma, osteoporosis, depression, myocardial infarction, diabetes I and II, any malignancy, and hospitalization with AECOPD or COPD in the prior year. Limitations: The study included only hospitalized AECOPD patients among prevalent COPD patients. Furthermore, information was lacking on clinical variables. Conclusion: These findings indicate that AECOPD hospitalizations are associated with substantial mortality and risk of recurrence.